2008
DOI: 10.1016/j.rmed.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training in adults with chronic obstructive pulmonary disease: An update of a systematic review

Abstract: The purpose was to update an original systematic review to determine the effect of inspiratory muscle training (IMT) on inspiratory muscle strength and endurance, exercise capacity, dyspnea and quality of life for adults with chronic obstructive pulmonary disease (COPD). The original MEDLINE and CINAHL search to August 2003 was updated to January 2007 and EMBASE was searched from inception to January 2007. Randomized controlled trials, published in English, with adults with stable COPD, comparing IMT to sham I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 37 publications
11
98
1
8
Order By: Relevance
“…overload, specificity and reversibility, have been shown to improve respiratory strength and endurance in healthy subjects (32) and in chronic respiratory disease (33). Training may also influence respiratory muscle endurance, dependent upon the training protocol.…”
Section: Respiratory Muscle Trainingmentioning
confidence: 99%
“…overload, specificity and reversibility, have been shown to improve respiratory strength and endurance in healthy subjects (32) and in chronic respiratory disease (33). Training may also influence respiratory muscle endurance, dependent upon the training protocol.…”
Section: Respiratory Muscle Trainingmentioning
confidence: 99%
“…The role of inspiratory muscle training (IMT) for individuals with stable COPD is unclear (Geddes, O'Brien, Reid, Brooks, & Crowe, 2008). The first systematic review on IMT found little evidence to support the use of IMT (Shoemaker, Donker, & Lapoe, 2009).…”
Section: Respiratory Muscle Trainingmentioning
confidence: 99%
“…Using IMT in combination with other interventions and using flow-dependent resistive training is important in the pulmonary rehabilitation program (Geddes et al, 2008). However, there are no established thresholds for what constitutes a clinically meaningful change in inspiratory muscle strength or endurance, other methods must be utilized to infer clinical benefit (Shoemaker et al, 2009).…”
Section: Types Of Intervention: Sham Low-and High-intensity Imtmentioning
confidence: 99%
“…33 This conclusion, however, was refuted by several later systematic reviews. [8][9][10] For example, Geddes et al 8 accounted for studies with methodological differences by examining threshold and targeted trainers separately from inspiratory resistive trainers with no target, and concluded that normocapneic hyperventilation, targeted inspiratory resistive, or threshold IMT significantly increased inspiratory muscle strength and endurance compared to sham IMT (see Table 1). The conflicting messages from the literature may have contributed to the confusion among physiotherapists with respect to this intervention (see Table 1).…”
Section: Research-related Factorsmentioning
confidence: 99%
“…1 Studies from Australia, 2,3 England, 3 Sweden, 4 the United States, 5,6 and Canada 7 have shown that physical therapists have a positive attitude toward EBP, but this attitude does not always translate into practice. For example, a variety of studies [8][9][10] have provided evidence supporting the use of inspiratory muscle training (IMT) for some people with chronic obstructive pulmonary disease (COPD), such as those who are unable to participate fully in whole-body exercise training because of comorbid conditions or those who have intractable dyspnea despite whole-body exercise. However, a survey of Canadian acute-care hospitals and pulmonary rehabilitation programmes found that less than 5% of physiotherapists prescribe IMT for COPD rehabilitation.…”
Section: Introductionmentioning
confidence: 99%